(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The various developments in the field of technology, changes in the auto industry met. Carbon emissions from vehicles play an important role in global warming, thus forcing to produce vehicles with zero carbon emissions or low carbon emissions. Thus, the production of electric vehicles attracts the same attention and many countries have advanced plans for this. This paper described, Electric vehicle, Hybrid electric vehicle, Plug in Hybrid vehicle, Fuel cell hybrid electric vehicle, Range extended electric vehicles, power train, energy management, and features.